PEDAGOGICAL CONDITIONS FOR IMPROVING SPECIAL TRAINING OF FOOTBALL REFEREES OF DIFFERENT QUALIFICATION LEVELS - ИСАКОВ Руслан Шавкатович; ТОШМУХАМЕДОВА Насиба Муроджон кизи («PHYSICAL CULTURE: UPBRINGING, EDUCATION, TRAINING», 2025)
The article is devoted to the study of the state of theoretical and practical knowledge, as well as the level of physical fitness of football referees of various qualifications. The authors have proven that special training must meet the high requirements of modern competitive activities. The importance of the initial stage of formation of professional qualities of a referee, characterized by a comprehensive approach and comprehensive development, is substantiated. Particular attention is paid to the training of football referees, since they determine the course of the game process and influence the final outcome of the competition.